Cas9-AAV6 gene correction of beta-globin in autologous HSCs improves sickle cell disease erythropoiesis in mice - Adam C. Wilkinson (Nature Portfolio, 2021)
CRISPR mediated gene correction of sickle cell disease (SCD) in patient-derived hematopoietic stem cells is a promising avenue for therapy. Here the authors use a humanized SCD mouse model to study gene editing in the context of autologous transplantation.